Contribution of the Endosomal-Lysosomal and Proteasomal Systems in Amyloid-β Precursor Protein Derived Fragments Processing - Evrard, Caroline; Kienlen-Campard, Pascal; Coevoet, Mathilde; Opsomer, Rémi; Tasiaux, Bernadette; Melnyk, Patricia; Octave, Jean-Noël; Buée, Luc; Sergeant, Nicolas; Vingtdeux, Valérie (Frontiers in Cellular Neuroscience, 2018)
Aβ peptides, the major components of Alzheimer’s disease (AD) amyloid deposits, are released following sequential cleavages by secretases of its precursor named the amyloid precursor protein (APP). In addition to secretases, degradation pathways, in particular the endosomal/lysosomal and proteasomal systems have been reported to contribute to APP processing. However, the respective role of each of these pathways toward APP metabolism remains to be established. To address this, we used HEK 293 cells and primary neurons expressing full-length wild type APP or the β-secretase-derived C99 fragment (β-CTF) in which degradation pathways were selectively blocked using pharmacological drugs. APP metabolites, including carboxy-terminal fragments (CTFs), soluble APP (sAPP) and Aβ peptides were studied. In this report, we show that APP-CTFs produced from endogenous or overexpressed full-length APP are mainly processed by γ-secretase and the endosomal/lysosomal pathway, while in sharp contrast, overexpressed C99 is mainly degraded by the proteasome and to a lesser extent by γ-secretase.